2020
DOI: 10.1016/j.amc.2020.125137
|View full text |Cite
|
Sign up to set email alerts
|

Computational and analytical studies of the Randić index in Erdös–Rényi models

Abstract: In this work we perform computational and analytical studies of the Randić index R(G) in Erdös-Rényi models G(n, p) characterized by n vertices connected independently with probability p ∈ (0, 1). First, from a detailed scaling analysis, we show that R(G) = R(G) /(n/2) scales with the product ξ ≈ np, so we can define three regimes: a regime of mostly isolated vertices when ξ < 0.01 (R(G) ≈ 0), a transition regime for 0.01 < ξ < 10 (where 0 < R(G) < n/2), and a regime of almost complete graphs for ξ > 10 (R(G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 39 publications
3
48
0
Order By: Relevance
“…The Randić Index of a graph has been introduced in 1976 by Milan Randić [57] to study molecular structures of organic chemistry compounds. Even though it is behind the aims of our investigation, from a mathematical viewpoint we highlight, as this index is still widely investigated for its properties as, for instance, in [62][63][64].…”
Section: Randić Indexmentioning
confidence: 99%
“…The Randić Index of a graph has been introduced in 1976 by Milan Randić [57] to study molecular structures of organic chemistry compounds. Even though it is behind the aims of our investigation, from a mathematical viewpoint we highlight, as this index is still widely investigated for its properties as, for instance, in [62][63][64].…”
Section: Randić Indexmentioning
confidence: 99%
“…For recent exceptions see Refs. [25,43,44], where the average Randić index has been used to probe the percolation transition in Erdös-Rényi graphs and RGGs.…”
Section: B Randić Connectivity Indexmentioning
confidence: 99%

Non-uniform random graphs on the plane: A scaling study

Martinez-Martinez,
Mendez-Bermudez,
Rodrigues
et al. 2021
Preprint
“…This statistical approach, well known in random matrix theory studies, has been recently applied to random networks by means of topological indices, see e.g. [18][19][20]. Moreover, it has been shown that average topological indices may serve as complexity measures equivalent to standard random matrix theory measures [21,22].…”
Section: Computational Study Of Sp α (G) On Random Networkmentioning
confidence: 99%